2020
DOI: 10.1103/physrevb.101.035144
|View full text |Cite
|
Sign up to set email alerts
|

Sparse sampling approach to efficient ab initio calculations at finite temperature

Abstract: Efficient ab initio calculations of correlated materials at finite temperature require compact representations of the Green's functions both in imaginary time and Matsubara frequency. In this paper, we introduce a general procedure which generates sparse sampling points in time and frequency from compact orthogonal basis representations, such as Chebyshev polynomials and intermediate representation (IR) basis functions. These sampling points accurately resolve the information contained in the Green's function,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 67 publications
1
106
0
Order By: Relevance
“…were developed to further improve numerical efficiency. [162][163][164] The method provides momentum-and frequency-dependent self-energies in the regime of weak to intermediate coupling strength and was successfully applied to multi-band high-Tc superconductors. [104,153,154] As for future work it might be interesting to extend multiorbital TPSC to study further neighbor interactions as was already done for the single-orbital TPSC [146][147][148] or superconductivity as was already started in ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were developed to further improve numerical efficiency. [162][163][164] The method provides momentum-and frequency-dependent self-energies in the regime of weak to intermediate coupling strength and was successfully applied to multi-band high-Tc superconductors. [104,153,154] As for future work it might be interesting to extend multiorbital TPSC to study further neighbor interactions as was already done for the single-orbital TPSC [146][147][148] or superconductivity as was already started in ref.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, new numerical techniques were developed to further improve numerical efficiency. [ 162–164 ] The method provides momentum‐ and frequency‐dependent self‐energies in the regime of weak to intermediate coupling strength and was successfully applied to multi‐band high‐Tc superconductors. [ 104,153,154 ]…”
Section: Discussionmentioning
confidence: 99%
“…While these do not by themselves change the computational and memory complexity of the solver, they yield a significant reduction in the constant associated with the scaling, and should be used in implementations. Also, in the equilibrium case, spectral methods and specialized basis representations have been used to represent Green's functions with excellent efficiency, and their applicability in the nonequilibrium case has not yet been explored [61,[99][100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed that the difference of J i j values at β = 200 and 400 eV −1 is less than 1%. We use the intermediate representation basis for the Matsubara frequency summation [79][80][81] and set the cutoff parameter = 10 5 , which is sufficiently larger than W β, where W is the bandwidth.…”
Section: E Calculation Conditionsmentioning
confidence: 99%